Successful Microneurovascular Penile Replantation Using Loupe Magnification Following Self Amputation in A Young Patient - Ahmed, Tanveer; Hossain, Zakir; Lenin, Lutfar Kader (Journal of Surgical Sciences, 2019)
Amputation of the penis is a rare condition reported from various parts of the world. They reported as isolated cases or small series of patients in scientific research. The common etiology is self amputation by sharp weapon or an avulsion or crush injury in an industrial accident or following violence. Complete reconstruction of anatomical structures should be done in one stage which provides the best chance for full rehabilitation of the patient. We report here a single case of sub-total amputation of the penis at it's proximal third in a schizophrenic patient. The penis was successfully replanted using a microsurgical technique. After surgery, near-normal appearance and function including a good urine flow and absence of urethral stricture, capabilities of erection and near normal sensitivity were observed. Journal of Surgical Sciences (2013) Vol. 17 (1) : 54-57